Decreased Levels of Insulin-Regulated Aminopeptidase (IRAP) in Gestational Diabetes Mellitus: A Prospective Cohort Study - Osman Köse; Koray Gök; Elif Köse; Sezen Irmak Gözükara; Abdullah Tüten; Mehmet Sühha Bostancı (Clinical and Experimental Obstetrics & Gynecology)
Background: Insulin-regulated aminopeptidase (IRAP) is involved in insulin sensitivity and glucose metabolism and is important in the pathophysiology of type 2 diabetes. Serum IRAP levels are strongly associated with type 2 diabetes and insulin resistance. The aim of this study was to evaluate the IRAP level as a potential biomarker for the early diagnosis and management of insulin resistance in women with gestational diabetes mellitus (GDM). Methods: This cohort study included 40 women with GDM and 40 women with healthy pregnancies. Maternal serum IRAP levels were measured with enzyme-linked immunosorbent assay (ELISA) and compared between the two groups. Results: The mean serum IRAP level was significantly lower in the GDM group (0.73 ± 0.12 ng/mL) compared to the controls (0.92 ± 0.10 ng/mL) (p = 0.001). Pairwise comparisons indicated, that diet modified and insulin treated GDM subgroups had significantly lower serum IRAP levels than the control group (p < 0.017 and p < 0.017, respectively). Serum IRAP levels showed significant negative correlations with fasting glucose, insulin, homeostatic model assessment of insulin resistance (HOMA-IR) levels and hemoglobin A1c (HbA1c) (r = –0.541, p = 0.001; r = –0.447, p = 0.001; r = –0.584, p = 0.001; r = –0.361, p = 0.001). The optimum serum IRAP cut-off value was calculated to be 0.857 ng/mL, with a sensitivity of 85% and a specificity of 80% for the prediction of GDM (p = 0.001). Conclusions: The serum IRAP level in pregnant women diagnosed with GDM was significantly lower than in healthy pregnant women. Moreover, the serum IRAP level was negatively correlated with the levels of insulin, HbA1c, and HOMA-IR. These findings suggest that low serum IRAP level could be a novel biomarker for the prediction of GDM. Clinical Trial registration: The study has been registered on https://classic.clinicaltrials.gov/ (registration number: NCT06716320).